A spoonful of sugar: Gamification as means for enhancing employee self-leadership and self-concordance at work - Richard A. Oxarart; Jeffery D. Houghton (Administrative Sciences, 2021)
Organizations today continue to seek new and effective ways to engage and motivate their workers. Gamification is an emerging means for enhancing employee engagement and motivation at work. Self-leadership is a comprehensive self-influence process that has the potential to help employees find meaning and purpose from their jobs. This paper develops and presents a conceptual model of the relationships between gamification, self-leadership, and valued workplace outcomes. The model suggests that gamification elements trigger multiple self-leadership processes and states that interact in a multiplicative fashion leading to a state of self-concordance in which individuals perceive a close alignment between their work tasks and their personal interests and core values. This serial mediation model helps to explain how and why gamification operates through the mediating mechanisms of self-leadership and self-concordance to effect important individual and organizational outcomes. Future research directions and implications for the proposed conceptual model are also discussed.
Keywords: 350; creativity; gamification; self-concordance; self-determination; self-efficacy; self-leadership